You need to use the equation that relates the old salary and the new increased salary such that:

`9936 = s + 15/100*s => 9936 = s + 0.15s`

Factoring out s yields:

`9936 = s(1 + 0.15) => s = 9936/1.15 => s = 8640`

**Hence, evaluatingthe initial salary, before being increased, yields `s = $8640` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now